A closed-loop recycling process for carbon fiber-reinforced polymer waste using thermally activated oxide semiconductors Carbon fiber recycling, characterization and life cycle assessment - Cheng, Huanbo (Waste management (New York, N.Y.), 2022)
Copyright © 2022 Elsevier Ltd. All rights reserved.